The Interplay between ESCRT and Viral Factors in the Enveloped Virus Life Cycle - Bo Meng; Andrew M. L. Lever (Viruses, 2021)
Viruses are obligate parasites that rely on host cellular factors to replicate and spread. The endosomal sorting complexes required for transport (ESCRT) system, which is classically associated with sorting and downgrading surface proteins, is one of the host machineries hijacked by viruses across diverse families. Knowledge gained from research into ESCRT and viruses has, in turn, greatly advanced our understanding of many other cellular functions in which the ESCRT pathway is involved, e.g., cytokinesis. This review highlights the interplay between the ESCRT pathway and the viral factors of enveloped viruses with a special emphasis on retroviruses.